Challenges and Opportunities in Multigrade Teaching: Experiences of Primary School Teachers in Far-Flung Schools - Rondero, , Clyde Polynne Mayden G.; Casupanan, Ivy H. (Future Science / FSH-PH Publications, 2024)
This study finds out the opportunities and challenges in multi-grade teaching: experiences of primary school teachers in far-flung schools in San Marcelino, Zambales. The study made use of qualita-tive research adhering to the phenomenological methods and data were thematically analyzed. Results of the study showed that the challenges encountered by multigrade teachers in far-flung schools are difficulty in handling classroom and time management, failing to consider the diversity of learners, inadequacy in teaching multi-ple grades and experiencing burnout in teaching. Multigrade teachers overcome challenges encountered through teachers’ re-sourcefulness, understanding differences, teachers’ resiliency, teachers’ innovativeness, and support group system Students use reappraising and evading as their boredom-coping strategies in Social Studies discussions. The opportunities experienced by the multigrade teachers are enhancing the self-esteem of teachers, recognizing shared responsibility for facilitating student learning and increasing the teaching proficiency of teachers. An enhance-ment program was proposed. The study recommends that the De-partment of Education (DepEd) may conduct seminars for good practices in teaching multigrade classes. Multigrade teachers may use varied teaching strategies and innovative instructional mate-rials that will cater all learners’ needs and for effective students’ learning. Further studies may be conducted to validate the results of the study.